2018
DOI: 10.1016/j.compositesb.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of RC beams using bottom and side NSM reinforcement

Abstract: The allowable strain in fibre reinforced polymers reinforcement is limited by design codes to avoid debonding. The near-surface mounted (NSM) reinforcement technique has been proven to produce better anchorage behaviour compared to externally bonded reinforcement solutions. However, NSM solutions do not always eliminate debonding issues, with concrete cover detachment (CCD) typically occurring in RC beams strengthened for flexure. This experimental study investigated the efficiency of side mounted (S) compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…To date, only a few studies have investigated the performance of side NSM FRP strengthening as that shown in Figure 1(d) (Hosen et al 2017;Hosen et al, 2018;Hosen et al, 2015;Imjai et al, 2020;Sabau et al, 2018;Sharaky et al, 2017;Shukri et al, 2016), and none of these studies has reported results from low-strength RC elements.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have investigated the performance of side NSM FRP strengthening as that shown in Figure 1(d) (Hosen et al 2017;Hosen et al, 2018;Hosen et al, 2015;Imjai et al, 2020;Sabau et al, 2018;Sharaky et al, 2017;Shukri et al, 2016), and none of these studies has reported results from low-strength RC elements.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the most common debonding failure observed in NSM systems is cover separation [134] (Fig. 14).…”
Section: Debonding Failurementioning
confidence: 95%
“…14). A side-NSM strengthened beam fails through concrete crushing with intermediate crack-induced debonding, which is ductile, compared to the concrete cover separation observed in a bottom NSM system [134]. The smooth surfaces of the NSM strips can result in lower adhesion between the strip and adhesives.…”
Section: Debonding Failurementioning
confidence: 99%
“…Pultruded carbon fiber-reinforced polymers (CFRPs) for near-surface mounted reinforcement (NSMR), as a means to strengthen concrete structures, has been used for several decades (e.g., [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]). The strengthening often results in a significant amount of benefits, namely lower additional permanent loads (CFRP is ~80% lighter than steel), possibility of mobilizing higher tensile strength (CFRP systems are approximately five times stronger than steel), excellent durability properties, installation easiness, among others.…”
Section: Introductionmentioning
confidence: 99%